The chemically peculiar double-lined spectroscopic binary HD 90264 - Quiroga, Claudio Hugo Martín (2010)
Context. HD 90264 is a chemically peculiar (CP) double-lined spectroscopic binary system of the type He-weak. Double-lined binaries are unique sources of data for stellar masses, physical properties, and evolutionary aspects of stars. Therefore, the determination of orbital elements is of great importance to study how the physical characteristics of CP stars are affected by a companion. Aims. We carried out a detailed spectral and polarimetric study of the spectroscopic binary system HD 90264 to characterize its orbit, determine the stellar masses, and investigate the spectral variability and possible polarization of the binary components. Methods. We employed medium-resolution echelle spectra and polarimetric data obtained at the 2.15-m telescope at CASLEO Observatory, Argentina. We measured radial velocities and line equivalent widths with IRAF packages. The radial velocity curves of both binary components were obtained combining radial velocity data derived from the single line of Hg ii λ3984 Å and the double lines of Mg ii λ4481 Å. Polarimetric data were studied by means of the statistical method of Clarke & Stewart and the Welch test. Results. We found that both components of the binary system are chemically peculiar stars, deficient in helium, where the primary is a He variable and the secondary is a Hg-Mn star. We derived for the first time the orbital parameters of the binary system. We found that the system has a quasi-circular orbit (e ∼ 0.04) with an orbital period of 15.727 days. Taking into account the circular orbit solution, we derived a mass ratio of q = MHe−w/MHg−Mn = 1.22. We also found a rotational period of around 15−16 days, suggesting a spin-orbit synchronization. Possible signs of intrinsic polarization have also been detected. Conclusions. HD 90264 is the first known binary system comprised of a He variable star as the primary component and a Hg-Mn star as the secondary one.